Screening of mitochondrial tRNA mutations in 300 infants with hearing loss - Tang, Kai; Gao, Ziying; Han, Chunling; Zhao, Suolin; Du, Xiaoyun; Wang, Wenjuan (Mitochondrial DNA. Part A. DNA mapping, sequencing, and analysis, 2019)
Mitochondrial DNA (MtDNA) mutations are the important causes for hearing loss. To see the contribution of mtDNA to deafness, we screened for mutations in mt-tRNA genes from 300 deaf infants and 200 healthy subjects. Moreover, we analyzed the mtDNA copy number and ROS levels in patients carrying the mt-tRNA mutations. Consequently, 3 mt-tRNA mutations: tRNA Leu(UUR) A3243G; tRNA Ala T5655C and tRNA Glu A14692G were identified, however, these mutations were not detected in controls. Of these, the A3243G mutation created a novel base-pairing (13G-23A) in the D-stem of tRNA Leu(UUR) ; while the T5655C mutation occurred at the very conserved acceptor arm of tRNA Ala ; in addition, the A14692G mutation was located at position 55 in the TΨC loop of tRNA Glu . Molecular analysis showed that patients harbouring the A3243G, T5655C and A14692G mutations had a lower level of mtDNA copy number, while ROS level increased significantly when compared with controls. Through the application of the pathogenicity scoring system, we noticed that the A3243G, T5655C and A14692G should be regarded as 'definitely pathogenic' mutations associated with deafness. Thus, our study provided novel insight into the pathophysiology, early detection of mitochondrial deafness.